Youth-led Social Entrepreneurship: Enabling Social Change - Clarke, Amelia; Dougherty, Ilona (Senate Hall, 2010)
The types of strategies and tactics a young social entrepreneur may pursue to create social change, as well as the social change they succeed in creating, are impacted by their capacity to deeply engage in traditional decision-making structures. This study considers two youth-led social enterprises, the strategies they pursue (socialization, influence or direct control) and the level of impact they achieve (individual, community/interorganizational, or systemic) and offers a framework of youth-led strategies for creating social change at different scales. The findings also provide insights into the innovative nature of these enterprises; and the implications for those wishing to enable more youth to become social entrepreneurs. Keywords: Social entrepreneurship, youth leadership, youth-led, social change, systemic change, impact, scale, Sierra Youth Coalition, Apathy is Boring, Canada
Keywords: social entrepreneurship|youth leadership|youth-led|social change|systemic change|impact|scale|Sierra Youth Coalition|Apathy is Boring|Canada